Simbolisme Religius dan Represi Estetik: Studi Kritis atas Dualisme Sastra di Pesantren - Mohammad Fikri (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Literature in the pesantren tradition functions not only as an aesthetic expression but also as a moral, spiritual, and ideological apparatus. This article critically explores the relationship between religious symbolism and aesthetic repression in the literary practices at a pesantren in Jember, focusing on the dichotomy between legitimized religious literature (such as nadhoman, Barzanji, Burdah, and Seket Aqoid) and repressed modern literature (such as novels and contemporary poetry). Using a qualitative case study design, the findings reveal that pesantren authorities construct a literary hierarchy through institutionalized values, moral surveillance, and the restriction of narrative forms perceived as misaligned with communal norms. Theoretical frameworks of symbolic power (Pierre Bourdieu), ideological apparatuses (Louis Althusser), and body discipline (Michel Foucault) illuminate how literature becomes a medium for subduing imagination and producing symbolic obedience. This article contributes to interdisciplinary discussions on literature, Islamic education, and cultural power within closed religious communities.